Burden of chronic obstructive pulmonary disease in China from 1990 to 2021: a population-based study - Wang, Xuefang; Liu, Jing; Li, Juan; Zhang, Ling; Zeng, Xiuqin; Cai, Ruijun (Frontiers in Medicine, 2025)
BackgroundChronic obstructive pulmonary disease (COPD) is associated with high prevalence, disability, and mortality rates. As one of the most populous countries facing a significant burden of COPD, the extent of this burden in China remains inadequately defined. This study utilizes data from the Global Burden of Disease Study 2021 (GBD 2021) to analyze the current status and trends of COPD burden in China, aiming to provide epidemiological data to support prevention, early intervention, and policy formulation related to COPD.MethodsThis study employs the GBD 2021 database and utilizes various statistical methods, including estimated annual percentage change, Joinpoint regression analysis, decomposition analysis, predictive analysis, and risk factor attribution, to conduct a stratified analysis of the burden of COPD in China by sex, age, and time.ResultsBetween 1990 and 2021, the age-standardized rate (ASR) of COPD in China showed a significant decline, with projections indicating that this trend will continue. However, the rate of decline has slowed in recent years, and the absolute number of COPD patients continues to rise. In 2021, the age-standardized incidence rate (ASIR) was 215.62 per 100,000, the age-standardized prevalence rate (ASPR) was 2,499.35 per 100,000, the age-standardized mortality rate (ASMR) was 73.23 per 100,000, and the age-standardized disability-adjusted life years (ASDR) was 1,227.66 per 100,000. The decline was more pronounced in females than in males, with females experiencing a lower overall burden. For both sexes, the ASR of COPD increased with age; prior to age 60, rates were similar, but after age 60, males exhibited higher ASMR and ASDR than females. Population aging is identified as the primary driver of the increasing burden of COPD, while epidemiological changes contribute to its reduction. Smoking remains the leading risk factor for mortality, with eight related risk factors identified.ConclusionWhile the ASR of COPD in China has significantly improved, the absolute burden continues to escalate, with notable differences by age and sex. Future efforts should focus on enhancing preventive measures for major risk factors and implementing early screening for high-risk populations to promote early diagnosis and treatment strategies, thereby alleviating the disease burden.